Обробка текстової інформації в режимі реального часу з використанням методів обчислювального інтелекту - Волкова, В.В.; Шубкіна, О.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The dedicated neural network that is a development of radial-basis structures was proposed. This neural network provides the issue decision of a named entities classification for building of semantic annotations for text documents of specified data domain. The model of neuro-fuzzy system for multi-topic text clustering was proposed. This model is based on an adaptive fuzzy selforganizing neural network.